Clinical Outcomes of Portosystemic Shunts on the Outcome of Liver Transplantation. Issue 5 (12th March 2020) - Rodriguez, Eduardo A.; Perez, Rachel; Zhang, Nan; Lim, Elisabeth S.; Miller, Christopher; Schwartz, Michael A.; McGirr, Aidan J.; Srinivasan, Ananth; Hewitt, Winston; Silva, Alvin C.; Rakela, Jorge; Vargas, Hugo E.
Abstract : Spontaneous portosystemic shunts (SPSSs) have been associated with worse clinical outcomes in the pre–liver transplantation (LT) setting, but little is known about their post‐LT impacts. Our aim was to compare LT candidates with and without SPSSs and assess the impact of SPSSs on patient mortality and graft survival in the post‐LT setting. Patients 18 years or older with abdominal imaging done prior to LT were included. Exclusion criteria were the presence of pre‐LT surgical shunts, LT indications other than cirrhosis, and combined solid organ transplantations. SPSSs were classified as absent, small, or large according to their maximum diameter (8 mm). Multiple variables that could influence the post‐LT course were extracted for analysis. Patient and graft survival were estimated using the Kaplan‐Meier method and were compared between groups using a log‐rank test. The project received institutional review board approval. We extracted data from 326 patients. After comparing patients without SPSS or with small or large SPSSs, no statistical difference was found for overall patient survival: no SPSS (n = 8/63), reference; small SPSS (n = 18/150), hazard ratio (HR), 1.05 (95% confidence interval [CI], 0.45‐2.46); and large SPSS (n = 6/113), HR, 0.60 (95% CI, 0.20‐1.78); P = 0.20. Also, no difference was found for graft survival: no SPSS (n = 11/63), reference; small SPSS (n = 21/150), HR, 0.80 (95% CI, 0.38‐1.70); large SPSS (n = 11/113), HR, 0.59 (95% CI, 0.25‐1.40); P = 0.48. Similarly, no statistical significance was found for these variables when comparing if the graft used was procured from a donation after circulatory death donor versus a donation after brain death donor. In conclusion, the previously described association between SPSSs and worse clinical outcomes in pre‐LT patients seems not to persist once patients undergo LT. This study suggests that no steps to correct SPSS intraoperatively are necessary.